Impact of dermal matrix thickness on split‐thickness skin graft survival and wound contraction in a single‐stage procedure. Issue 2 (9th July 2021) - Kemp Bohan, Phillip M.; Cooper, Laura E.; Fletcher, John L.; Corkins, Christopher J.; Natesan, Shanmugasundaram; Aden, James K.; Carlsson, Anders; Chan, Rodney K.
Abstract: Optimal treatment of full‐thickness skin injuries requires dermal and epidermal replacement. To spare donor dermis, dermal substitutes can be used ahead of split‐thickness skin graft (STSG) application. However, this two‐stage procedure requires an additional general anaesthetic, often prolongs hospitalisation, and increases outpatient services. Although a few case series have described successful single‐stage reconstructions, with application of both STSG and dermal substitute at the index operation, we have little understanding of how the physical characteristics of dermal substitutes affects the success of a single‐stage procedure. Here, we evaluated several dermal substitutes to optimise single‐stage skin replacement in a preclinical porcine model. A porcine full‐thickness excisional wound model was used to evaluate the following dermal substitutes: autologous dermal graft (ADG; thicknesses 0.15‐0.60 mm), Integra (0.4‐0.8 mm), Alloderm (0.9‐1.6 mm), and chitosan‐based hydrogel (0.1‐0.2 mm). After excision, each wound was treated with either a dermal substitute followed by STSG or STSG alone (control). Endpoints included graft take at postoperative days (PODs) 7 and 14, wound closure at POD 28, and wound contracture from POD 28‐120. Graft take was highest in the STSG alone and hydrogel groups at POD 14 (86.9% ± 19.5% and 81.3% ± 12.3%, respectively; P < .001). There were no differences in graft take at POD 7 or in wound closure at POD 28, though highest rates of wound closure were seen in the STSG alone and hydrogel groups (93.6% ± 9.1% and 99.8% ± 0.5%, respectively). ADG‐treated wounds demonstrated the least amount of wound contracture at each time point. Increase dermal substitute thickness was associated with worse percent graft take at PODs 14 and 28 (Spearman ρ of −0.50 and −0.45, respectively; P < .001). In this preclinical single‐stage skin reconstruction model, thinner ADG and hydrogel dermal substitutes outperformed thicker dermal substitutes. Both substitute thickness and composition affect treatment success. Further preclinical and clinical studies to optimise this treatment modality are warranted.